Backstepping Sliding Mode Control for Inverted Pendulum System with Disturbance and Parameter Uncertainty - Alfian Ma'arif; Marco Antonio Márquez Vera; Magdi Sadek Mahmoud; Samir Ladaci; Abdullah Çakan; Jonattan Niño Parada (Universitas Muhammadiyah Yogyakarta, 2022)
The inverted pendulum system is highly popular in control system applications and has the characteristics of unstable, nonlinear, and fast dynamics. A nonlinear controller is needed to control a system with these characteristics. In addition, there are disturbances and parameter uncertainty issues to be solved in the inverted pendulum system. Therefore, this study uses a nonlinear controller, which is the backstepping sliding mode control. The controller is robust to parameter uncertainty and disturbances so that it is suitable for controlling an inverted pendulum system. Based on testing with step and sine reference signals without interference, the controller can stabilize the system well and has a fast response. In testing with disturbances and mass uncertainty, the backstepping sliding mode controller is robust against these changes and able to make the system reach the reference value. Compared with sliding mode control, backstepping sliding mode control has a better and more robust response to disturbances and parameter uncertainty.